Programmed cell death in human respiratory syncytial virus infection - Yao, Pengyu; Ma, Chang; Liu, Chao (Frontiers in Cellular and Infection Microbiology, 2025)
PurposeViral infections elicit different forms of host cell death. Indeed, pathways of programmed cell death (PCD) have emerged as central events in the pathogenesis of various viruses. Regulating PCD is also a critical factor in the pathogenesis of respiratory syncytial virus (RSV) infection. This review systematically summarizes the mechanisms and pathological significance of the main PCD pathways related to RSV infection, and aims to deepen the understanding of RSV regulation of PCD. These findings may provide a new insights and potential therapeutic strategies for the precise prevention and treatment of RSV-related diseases.MethodologyThis review provides a comprehensive overview of the historical development of different forms of PCD. A systematic review was conducted across major academic databases, including Elsevier, PubMed, Springer, Google Scholar, and Web of Science, to collect studies related to RSV and PCD, published between the inception of each database and September 2025. The collected studies were then categorized and organized according to PCD type and affected cell type.ResultsIn RSV infection, there are a total of five types of PCD identified, including apoptosis, necroptosis, pyroptosis, NETosis, and ferroptosis. Among these, apoptosis is the most frequently regulated form of cell death during RSV infection. A variety of cell types undergo different forms of PCD during RSV infection, including airway epithelial cells, macrophages, neutrophils, dendritic cells (DCs), lymphocytes and neuronal cells. Notably, PCD is related to airway epithelial cells, which is the most common type of PCD.ConclusionsPCD serves as a central link in the interaction between RSV infection and the host cell. Different PCD pathways (apoptosis, necroptosis, pyroptosis, NETosis, and ferroptosis) play a dual role in RSV pathogenesis; however, the complex relationship between RSV and PCD remains unclear. Further studies are warranted to explore new forms of PCD in RSV infection, as well as the complex relationship between PCD and RSV structure, the cross-regulatory mechanisms between different PCDs, and the variability of PCD in different cell types. Targeted intervention strategies based on PCD pathways may provide new targets and treatment options for RSV-related diseases.